Gas reforming and tar decomposition performance of nickel oxide (NiO)/SBA-15 catalyst in gasification of woody biomass. (3rd April 2019) - Inoue, Naoko; Tada, Toshiya; Kawamoto, Katsuya
ABSTRACT: In the gasification of biomass, it is necessary to limit the amount of by-product tar and increase the yields of hydrogen (H2 ) and carbon monoxide (CO) (syngas). Therefore, we conducted gasification and reforming experiments on woody biomass using an electric tubular furnace, to evaluate the gas reforming and tar decomposition performance of a NiO/SBA-15 catalyst. As a result, we found that this catalyst is effective for H2 production. It is believed that the increase in H2 volume due to the catalyst occurs through a steam reforming reaction involving hydrocarbons, including methane (CH4 ), and the water-gas shift reaction. With respect to the influence of the gasifying agent on the reforming effect of the catalyst, the amount of generated carbon dioxide (CO2 ) and hydrogen (H2 ) increases because the shift reaction is promoted by supplying steam. On the other hand, it was inferred that the shift reaction rarely occurred because it approaches equilibrium by supplying O2 . Furthermore, it is suggested that light aromatic hydrocarbons are decomposed by the catalyst. Implications: The mesoporous silica catalyst NiO/SBA-15 was highly effective for H2 production and decomposition of light aromatic compounds in the gasification of woody biomass. In the catalyst reaction, supplying steam promoted H2 production. From thermodynamic analysis and discussion, it was also inferred that supplying O2 might prevent the water gas shift reaction. The results are useful for designing a process needed for rich H2 production and gas refining process for further use of syngas.